Sultan Jalaliddin Manguberdi's Struggle Against the Mongolia Invasion (Zien Journal of Social Sciences and Humanities, 2022)
This article gives a brief overview of Jalaliddin Manguberdi's martial arts and martial arts. This article is intended for students of higher and secondary special education institutions to get acquainted with the secrets of martial arts